Visible-light-drived high photocatalytic activities of Cu/g-C3N4 photocatalysts for hydrogen production. Issue 41 (8th April 2016) - Fan, Mingshan; Song, Chengjie; Chen, Tianjun; Yan, Xu; Xu, Dongbo; Gu, Wei; Shi, Weidong; Xiao, Lisong
Abstract : The Cu/g-C3 N4 photocatalysts presented here show excellent performance for H2 evolution in the absence of a noble-metal cocatalyst. Abstract : Cu/g-C3 N4 photocatalysts have been synthesized using a facile method. The composition and morphology of the prepared samples were characterized by a variety of analytical methods. The results indicate that the Cu nanoparticles were uniformly loaded onto the surface of g-C3 N4 . In addition, photocatalytic activity experiments were carried out by investigating H2 production under visible light irradiation. The results reveal that the composites exhibited excellent performance for H2 evolution in the absence of a cocatalyst, which demonstrates that Cu nanoparticles could trap photogenerated electrons and act as a cocatalyst effectively. Thus, it was effective in transferring the interfacial photogenerated charge carriers and efficiently enhanced the photocatalytic activity.